Overcoming Traffic Congestion - Darren M. Scott (European Journal of Transport and Infrastructure Research, 2002)
This paper addresses the issue of why measures designed to ease traffic congestion have met with limited success in North American cities. To this end, specific types of supply and demand strategies (i.e., roadway construction, jobs-housing balance and the compressed workweek) are discussed emphasizing behavioral responses to them. With respect to roadway construction, evidence of induced travel from recent studies undertaken in the United States is presented. With respect to the two remaining strategies, two studies conducted in Canada employing simulation models are described. Finally, activity-based travel demand models are discussed as a promising means for forecasting both anticipated and unanticipated behavioral responses to mitigation measures, thereby enabling policy makers to make informed decisions as to whether the measures merit implementation.